2004
DOI: 10.1590/s0100-879x2004000600005
|View full text |Cite
|
Sign up to set email alerts
|

A model of chronic IgE-mediated food allergy in ovalbumin-sensitized mice

Abstract: Food allergy is most frequently the result of IgE-mediated hypersensitivity reactions. Here, we describe a chronic model in which some of the intestinal and systemic consequences of continuous egg white solution ingestion by ovalbumin-sensitized eight-week-old BALB/c mice, 6 animals per group, of both sexes, were investigated. There was a 20% loss of body weight that began one week after antigen exposure and persisted throughout the experiment (3 weeks). The sensitization procedure induced the production of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 20 publications
5
39
0
1
Order By: Relevance
“…Also the positive controls developed high levels of all antibody subclasses, which is in line with previous studies [31,32]. Comparable to this route, even subcutaneous immunizations with OVA adsorbed to aluminum hydroxide were reported to induce high levels of IgG1 and IgE [33,34]. Furthermore, in our experiments both immunization regimens, i.p.…”
Section: Discussionsupporting
confidence: 92%
“…Also the positive controls developed high levels of all antibody subclasses, which is in line with previous studies [31,32]. Comparable to this route, even subcutaneous immunizations with OVA adsorbed to aluminum hydroxide were reported to induce high levels of IgG1 and IgE [33,34]. Furthermore, in our experiments both immunization regimens, i.p.…”
Section: Discussionsupporting
confidence: 92%
“…20 Cobalt-or vehicle-treated rats were injected with 20 mg/kg Evans blue via tail vein. After 20 min, kidneys were removed and the cortex dissected.…”
Section: Evaluation Of Vascular Permeabilitymentioning
confidence: 99%
“…Therefore, our group has developed a murine model of food allergy to ovalbumin (OVA) in which sensitized mice are challenged orally for 7 days. In this model, several signals similar to those that occur in patients with food allergy are developed, such as antigenic aversion, increased anti-OVA IgE production, intestinal oedema and intestinal eosinophil infiltration, as well as a marked weight and adipose tissue loss [13,14]. In addition, we have demonstrated that this allergic process induces an adipose tissue inflammation with an increase in the number of inflammatory cells and proinflammatory cytokine levels in this tissue, resulting in systemic metabolic alterations including the decrease in the serum glucose, triglycerides and total cholesterol [14].…”
Section: Introductionmentioning
confidence: 99%